Sustainable Tourism Destination Management Strategy: Improving Service Quality and Visitor Satisfaction: Strategi Pengelolaan Destinasi Wisata Berkelanjutan: Meningkatkan Kualitas Layanan dan Kepuasan Pengunjung - Ramdhan Kurniawan; Faridah Iriani; Minrohayati (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
Taman Kota 1 BSD is one of the green open spaces that has great potential to be developed as a sustainable tourism destination. This article discusses sustainable management efforts at Taman Kota 1 BSD which include improving the quality of facilities, empowering local communities, and applying digital technology for promotion and management. Through service activities that actively involve the community, there is a significant increase in key indicators such as visitor satisfaction, community participation, and environmental awareness. Survey results show that facility and service improvements, community training, and the use of digital technology have successfully improved the quality of this tourist destination. In addition, waste management and environmental education programs also contribute to environmental sustainability. With a holistic strategic approach, Taman Kota 1 BSD is expected to continue to be a model of a sustainable tourist destination that provides economic, social, and environmental benefits to the surrounding community. Abstrak Taman Kota 1 BSD merupakan salah satu ruang terbuka hijau yang memiliki potensi besar untuk dikembangkan sebagai destinasi wisata berkelanjutan. Artikel ini membahas upaya pengelolaan berkelanjutan di Taman Kota 1 BSD yang mencakup peningkatan kualitas fasilitas, pemberdayaan masyarakat lokal, dan penerapan teknologi digital untuk promosi dan manajemen. Melalui kegiatan pengabdian yang melibatkan masyarakat secara aktif, terjadi peningkatan signifikan pada indikator utama seperti kepuasan pengunjung, partisipasi masyarakat, dan kesadaran lingkungan. Hasil survei menunjukkan bahwa peningkatan fasilitas dan layanan, pelatihan masyarakat, serta penggunaan teknologi digital telah berhasil meningkatkan kualitas destinasi wisata ini. Selain itu, program pengelolaan sampah dan edukasi lingkungan juga berkontribusi pada keberlanjutan lingkungan. Dengan pendekatan strategis yang holistik, Taman Kota 1 BSD diharapkan dapat terus menjadi model destinasi wisata berkelanjutan yang memberikan manfaat ekonomi, sosial, dan lingkungan bagi masyarakat sekitar..